Psychometric evaluation of the healthy aging instrument in older adults. Issue 6 (3rd June 2021) - Yildirim, Hilal; Isik, Kevser; Cengizhan, Sıdıka Özlem
ABSTRACT: This methodological study was conducted for the psychometric evaluation of the Healthy Aging Instrument in older adults. The study was carried out with 430 older adults registered at two family health centers. The results of the Kaiser–Meyer–Olkin Measure of Sampling Adequacy and the Bartlett's test, which was used to determine the suitability of the measurement tool for factor analysis, were found as .83 and .000, respectively. The Cronbach's alpha value of the instrument was found as .88. As a result of the construct validity analysis, the scale consisted of 8 factors with 31 items. The Healthy Aging Instrument had sufficient internal consistency reliability and construct validity. The results were considered suitable for a scale adapted to Turkish. As the study is limited to the region where the scale was applied, further psychometric tests should be performed in different countries considering cultural varieties.